Antitumor effect of plant-produced anti-CTLA-4 monoclonal antibody in a murine model of colon cancer - Bulaon, Christine Joy I.; Khorattanakulchai, Narach; Rattanapisit, Kaewta; Sun, Hongyan; Pisuttinusart, Nuttapat; Strasser, Richard; Tanaka, Shiho; Soon-Shiong, Patrick; Phoolcharoen, Waranyoo (Frontiers in Plant Science, 2023)
Cytotoxic T lymphocyte-associated protein 4 (CTLA-4) is an immune checkpoint regulator exclusively expressed on T cells that obstructs the cell’s effector functions. Ipilimumab (Yervoy®), a CTLA-4 blocking antibody, emerged as a notable breakthrough in modern cancer treatment, showing upfront clinical benefits in multiple carcinomas. However, the exhilarating cost of checkpoint blockade therapy is discouraging and even utmost prominent in developing countries. Thereby, affordability of cancer care has become a point of emphasis in drug development pipelines. Plant expression system blossomed as a cutting-edge platform for rapid, facile to scale-up, and economical production of recombinant therapeutics. Here, we describe the transient expression of an anti-CTLA-4 2C8 antibody in Nicotiana benthamiana with yields of up to 39.65 ± 8.42 µg/g at 4 days post-infiltration. ELISA and bio-layer interferometry analyses show that plant-produced anti-CTLA-4 2C8 mAb exhibit cross-species binding to both human and murine CTLA-4 and that the plant-produced IgG1 also binds to human FcγRIIIa. In addition, the plant-produced 2C8 mAb is as effective as Yervoy® in inhibiting tumor growth in vivo. In conclusion, our study underlines the applicability of plant platform to produce functional therapeutic antibodies with promising potential in cancer immunotherapy.